2014
DOI: 10.1371/journal.pntd.0002799
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices Related to Visceral Leishmaniasis in Rural Communities of Amhara State: A Longitudinal Study in Northwest Ethiopia

Abstract: BackgroundIn the northwest of Ethiopia, at the South Gondar region, there was a visceral leishmaniasis (VL) outbreak in 2005, making the disease a public health concern for the regional health authorities ever since. The knowledge on how the population perceives the disease is essential in order to propose successful control strategies.Methodology/Principal findingsTwo surveys on VL knowledge, attitudes and practices were conducted at the beginning (May 2009) and at the end (February 2011) of a VL longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
(37 reference statements)
3
17
0
1
Order By: Relevance
“…And compared to attitude, knowledge had a higher correlation with the participants' practice. The findings of the present study indicated that the knowledge of the participants in the study was below average and this was consistent with the findings of previous studies [13,14] but it was not consistent with the study by Alemu [15]. Low awareness of the people about leishmaniasis is a serious alarm due to the rising trend of the disease in recent years and also, the serious and close attention of the Ministry of Health and universities of Medical Sciences on leishmaniasis is requured.…”
Section: Resultssupporting
confidence: 61%
“…And compared to attitude, knowledge had a higher correlation with the participants' practice. The findings of the present study indicated that the knowledge of the participants in the study was below average and this was consistent with the findings of previous studies [13,14] but it was not consistent with the study by Alemu [15]. Low awareness of the people about leishmaniasis is a serious alarm due to the rising trend of the disease in recent years and also, the serious and close attention of the Ministry of Health and universities of Medical Sciences on leishmaniasis is requured.…”
Section: Resultssupporting
confidence: 61%
“…However, the adoption of preventive measures strongly depends on the attitudes and behaviors of the population at risk. Therefore, in order to control leishmaniasis, it is essential to know the risk factors associated with it, and to understand the disease-related knowledge, attitudes, and practices (KAP) of the population [ 7 ]. Studies in Colombia revealed a direct relationship between awareness of the population at risk and adoption of preventive measures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…De fato, o presente estudo detectou essa transição entre os anos de 2007 e 2016 na área estudada, visto que a proporção de acometidos residentes em zonas urbanas aumentou significativamente quando comparado aos anos anteriores (2001)(2002)(2003)(2004)(2005)(2006). Aliado a isso, provavelmente está o aumento de LV também observado entre indivíduos com alto nível de escolaridade, que usualmente são menos encontrados na zona rural (LÓPEZ-PEREA et al, 2014).…”
Section: Discussionunclassified